Lisboa en primavera: desde la Revolución de los Claveles a la Lisboa de hoy - BOUZA, Fermín (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
This article collects the memories that link the author with the city of Lisbon and some historic and legendary references.